KESEJAHTERAAN PSIKOLOGIS PADA JEMAAH PENGAJIAN DITINJAU DARI RELIGIUSITAS DAN HUBBUD DUNYA - Lavenda Azalia; Leli Nailul Muna; ahmad Rusdi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
Psychological well-being is an important psychological element that supports individual total functioning. Psychological well-being is influenced by various factors including religiosity, and inversely proportional to psychological illness such as depression, anxiety, and materialism. This study aims to test the hypothesis of the relationship between hubbud dunya and religiosity with psychological well-being in the congregation of pengajian. The sample in this study is the congregation of pengajian by sampling method using purposive sampling. Methods of data collection using 4 scales of research. The psychological well-being scale of Ryff (1995), the scale of religiosity 1 and 2 of Nashori & Wijaya (2016), and the scale of hubbud dunya compiled by researchers based on Imam al-ghazali thought in ihya 'ulumuddin. Data analysis using spearman correlation coefficient test. The results showed there was a positive relationship between religiosity and psychological well-being. The aspects of religiosity that has a positive relationship with psychological well-being is the aspect of worship, morals, and experience. The hypothesis test between hubbud dunya and psychological well-being showed that there was no significant relationship between the two.